1995
DOI: 10.2307/3392272
|View full text |Cite
|
Sign up to set email alerts
|

Lectotypification of Kengyilia mutica (Keng ex Keng & S. L. Chen) J. L. Yang, Yen & Baum (Poaceae), and Change of Circumscription

Abstract: A lectotype of Kengyilia mutica (Keng ex Keng & S. L. Chen) J. L. Yang, Yen & Baum is here designated based on an illustration of the holotype; the latter has been lost. A more complete description than the original, which was based on a single and incomplete specimen, is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…One maser line that is studied in massive star forming regions corresponds to the F = 3 − − 3 + hyperfine transition of the 2 Π 3/2 (J = 5/2) excited state of OH at a frequency of 6.035 GHz (Knowles et al 1976). First detected by Yen et al (1969) toward W3(OH), maser lines from this transition have been found associated with massive star formation in galactic and extragalactic environments (Caswell & Vaile 1995;Caswell 1995). The 6.035 GHz OH line shows a large flux density range in galactic maser sources, from more than 100 Jy to ∼ 0.1 Jy (e.g., Baudry et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…One maser line that is studied in massive star forming regions corresponds to the F = 3 − − 3 + hyperfine transition of the 2 Π 3/2 (J = 5/2) excited state of OH at a frequency of 6.035 GHz (Knowles et al 1976). First detected by Yen et al (1969) toward W3(OH), maser lines from this transition have been found associated with massive star formation in galactic and extragalactic environments (Caswell & Vaile 1995;Caswell 1995). The 6.035 GHz OH line shows a large flux density range in galactic maser sources, from more than 100 Jy to ∼ 0.1 Jy (e.g., Baudry et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In the cationic species, the amine salt (of P-40) did not show any peaks above the region of 3200 cm 21 indicating the lack of the hydrogen bonded interaction in the absence of the BOC pendant. 43,50,51 To further confirm this trend, DLS histograms of the neutral P-40 nanoparticles that were incubated at pH 5 7.4, 6.0, 4.0, and 2.0 for 12 h were recorded and are shown in Figure 4(c). The size of the nanoparticle was observed to increase gradually from 350 nm (in pH 5 7.4) to 750 nm (in pH 5 2.0) with increase in the acidic environment [ Figure 4(c)].…”
Section: Transformation Into Cationic Polyestermentioning
confidence: 73%
“…Aromatic-aliphatic polyester-amides (PEAs) are well known for exhibiting liquid-crystalline properties because of the intermolecular hydrogen bonding between amide-amide and amide-ester moieties. [1][2][3][4][5][6][7][8][9][10][11][12] We have previously shown that amido diol can be used as an important precursor for the synthesis of novel PEAs containing inbuilt diamide linkage and that the extensive hydrogen bonds between the amide-amide and amide-ester groups stabilize the mesophase structures of PEAs. [7][8][9][10][11][12] The generation and stabilization of the mesophase is further enhanced because of the rigidity of the aromatic ring and the double-bond character of the carbonyl group of the amide linkage.…”
Section: Introductionmentioning
confidence: 99%